On the Mexican trapdoor spiders: description of a new species of the spider genus Eucteniza Ausserer (Araneae, Mygalomorphae, Euctenizidae) from the western coast of Mexico - Valdez-Mondragón, Alejandro; Jiménez, Maria Luisa (Zootaxa, 2024)
The trapdoor spider genus Eucteniza Ausserer, 1875 is distributed in North America, with most diversity in Mexico. In this work, a new species is described from the Chamela-Cuixmala Biosphere Reserve, Jalisco, Mexico: Eucteniza cuixmala sp. nov., was collected from a dry tropical deciduous forest in the western coast of Mexico. The species is described only from the male holotype. Of the 14 species of Eucteniza described so far, eight have been described based only on the male holotype. The description of this new species increases the diversity of the genus to 15 known species, 14 of which are found in Mexico, two in the USA, and one in both countries: E. relata (O. Pickard-Cambridge, 1895). In addition, we provide an amended taxonomic identification key for males of the genus.